Intestinal Obstruction following Ingestion of Metallic Instruments in a Psychiatric Patient - Oscar Kivike; Israel Soko; David Mgaya; Frank Sandi (Case Reports in Surgery)
Pica among psychiatric patients has been well documented. We report a 25-year-old female patient who presented with abdominal distension for one week. She is a known psychiatric patient for 5 years. Through history taking, physical examination, and investigations, the patient was found to have psychotic features and features of intestinal obstruction. Surgery was done by opening the abdomen and then the stomach. The stomach, together with the proximal intestine, was found to be filled with metallic instruments weighing 780 mg. The diagnosis of a metalophagia type of pica was reached. All instruments were removed and the patient did well postoperatively.